Data Protection Impact Assessments as rule of law governance mechanisms. (2020) - Harris, Swee Leng
Abstract: Rule of law principles are essential for a fair and just society and apply to government activities regardless of whether those activities are undertaken by a human or automated data processing. This article explores how Data Protection Impact Assessments (DPIAs) could provide a mechanism for improved rule of law governance of data processing systems developed and used by government for public purposes in civil and administrative areas. Applying rule of law principles to two case studies provides a sketch of the issues and concerns that this article's proposals for DPIAs seek to address. The article undertakes comparative analysis to find relevant principles and concepts for governance of data processing systems, looking at human rights impact assessments, administrative law, and process rights in environmental law. Drawing on this comparative analysis to identify specific recommendations for DPIAs, the article offers guidance on how DPIAs could be used to strengthen the governance of data processing by government in rule of law terms. Policy Significance Statement: Data Protection Impact Assessments (DPIAs) are a relatively new development in the governance of data processing. The recommendations in this article are a tool for policy-makers and civil servants developing data processing systems for government and undertaking DPIAs, to assist government to meet rule of law standards when implementing new data processing systems. The article also adds to analysis of the governance of data processing systems for all stakeholders, including civil society.